UNSUSTAINABLE URBAN SPRAWL IN BRASILIA DF - LUZIÂNIA, ÁGUAS LINDAS DE GOIÁS AND VALPARAÍSO DE GOIÁS 2003-2014 - Carrillo Salomón, Yvette Mónica (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2019)
This article examines the urban expansion on Brazilian areas: Federal District, Luziânia, ÁguasLindasand Valparaíso de Goiás, in the period from 2003 to 2014. The study was conducted using the technological platform of ArcGis 10.1 which was employed to help in theanalysis of the urban sprawl. The result showed that the urban expansion evolves unsustainably lacking urban and environmental planning. This fact places a considerable risk not only the environmental balance but also the health of the dwellers in these places and surroundings.